profile
Опубликовано 1 год назад по предмету Алгебра от Yankasya

Решить уравнения:
1) x+3√x-10=0
2) (x-3)^4-7(x-3)^2-8=0

  1. Ответ
    Ответ дан Аккаунт удален
    х+3√х-10=9

    (√х)²+3√х-10=0

    пусть √х=t (t≥0)

    t²+3t-10=0
    a=1; b=3; c=-10

    D=b²-4ac=3²-4*1*(-10)=49
    √D=7

    t1=(-b-√D)/2a=(-3-7)/2=-5
    t2=(-b+√D)/2a=(-3+7)/2=2

    t1=-5 - ∅ при t≥0

    замена

    √x=2
    x=4

    Ответ: 4.

    (х-3)⁴-7(х-3)²-8=0

    Пусть (x-3)²=t (t≥0)

    t²-7t-8=0
    a=1;b=-7;c=-8

    D=b²-4ac=(-7)²-4*1*(-8)=49+32=81

    √D=9

    t1=(-b-√D)/2a=(7+9)/2=8
    t2=(-b+√D)2a=(7-9)/2=-1 - ∅

    замена

    (х-3)²=8
    х-3=√8
    х1=√8+3
    х-3=-√8
    х=-√8+3

Самые новые вопросы